(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The purpose of the research was to investigate the intervention of yoga on handgrip strength among male adolescent recurve archers. Both the experimental group and the control group were investigated. A total of twenty archery players were separated into two groups: the experimental group received ten participants, while the control group received other ten participants. The ages of the participants ranged from 14 to 17 years. Only participants in the experimental group were given the yoga intervention, and hand grip strength was measured before and after the yoga intervention. The handgrip was analyzed with the use of qingfeng hand dynamometer, which has been regarded as a trustworthy instrument and test for determining the relevant parameter. The gathered information was subjected to statistical examination using analysis of covariance. The results revealed that sixteen weeks of yoga practice considerably improved handgrip strength among male adolescent recurve archers.